USING SHORT FILMS FOR TEACHING ENGLISH WHILE BUILDING CHARACTERS - Hutapea Jesica Vanessa; Suwastini Ni Komang Arie (Lingua Scientia, 2019)
The role of teachers in EFL/ESL classroom is very important for the improvement of the students since it is believed that professional and creative English teachers can help students in learning English well. However, many teachers still lack the effort in finding new ideas and in improving their professionalism as a good English teacher. Yet, with the development of technology nowadays, many media are worth to be considered in teaching English. One of the media that is being actively mentioned in educational world nowadays is short film. In this case, short film is believed to be one of the appropriate ways in teaching English especially in teaching the character education presented in it. With short film, students can have more exposure to authentic English and the culture of the target language. But another important benefit is often overlooked by teachers, that is the possibility of learning values for building the students’ characters through the use of short film in the learning process. This present paper will try to respond to this fact by identifying the values of character educations in a short film entitled Piper from Pixar animation through textual analysis. There are character educations that revealed about parenting, self-supporting, and friendship value in the film. Thus, it can be concluded that when chosen correctly, short films can be a media for building students’ characters while developing their English, all in a more entertaining, relaxed, and enjoyable media that meet the students’ 21st century contexts.